AMH prevents primordial ovarian follicle loss and fertility alteration in cyclophosphamide‐treated mice. Issue 1 (16th August 2018) - Sonigo, Charlotte; Beau, Isabelle; Grynberg, Michael; Binart, Nadine
ABSTRACT: The follicular ovarian reserve, constituted by primordial follicles (PMFs), is established early in life, then keeps declining regularly along reproductive life. The maintenance of a normal female reproductive function implies the presence of a vast amount of dormant PMFs. This process involves a continuous repression of PMF activation into early growing follicle through the balance between factors activating the initiation of follicular growth, mainly actors of the PI3K signaling pathway, and inhibiting factors such as anti‐Müllerian hormone (AMH). Any disruption of this balance may induce follicle depletion and subsequent infertility. It has been recently proposed that cyclophosphamide (Cy), an alkylating agent commonly used for treating breast cancer, triggers PMF activation, further leading to premature ovarian insufficiency. Preventing chemotherapy‐induced ovarian dysfunction might represent an interesting option for preserving optimal chances of natural or medically assisted conceptions after healing. The aim of the present study was to evaluate, in a model of Cy‐treated pubertal mice, whether AMH administration might restrain PMF depletion. The counting of the total PMF number within mouse ovaries showed that recombinant AMH prevented Cy‐induced PMF loss. Western blot analysis revealed activation of PI3K signaling pathway after Cy administration. After AMH injection, FOXO3A phosphorylation, a main actor of PMF activation, was significantly decreased. Taken together, these results support a protective role of AMH against Cy‐induced follicular loss. We also provide evidence for a possible role of autophagy in the preservation of follicular pool reserve. Therefore, concomitant recombinant AMH administration during chemotherapy might offer a new option for preserving young patients' fertility.—Sonigo, C., Beau, I., Grynberg, M., Binart, N. AMH prevents primordial ovarian follicle loss and fertility alteration in cyclophosphamide‐treated mice. FASEB J. 33, 1278–1287 (2019). www.fasebj.org